PTU-067 Helicobacter pylori resistance: a complex socioeconomic problem?. (June 2019) - Sullivan, Luke; Zakeri, Nekisa; Negus, Rupert; Mack, Damien; Morgan, Marsha Y
Abstract : Introduction: Helicobacter pylori ( H. pylori ) infection is the primary cause of peptic ulcer disease and is globally prevalent. Although eradication therapy is effective, emerging antibiotic resistance rates are of considerable concern. H. pylori infection is more prominent in deprived populations but the effects of ethnicity and social determinants of health on H. pylori resistance is unclear. The aim of this study was to establish the significance of socioeconomic and ethnic influences on H. pylori resistance. Methods: The study population comprised of patients with recurrent/previous H. pylori infection plus current dyspeptic symptoms referred to the Royal Free Hospital, London, from 1 January 2017 to 1 September 2018, for endoscopic investigations. Gastro/duodenal biopsy samples were sent for culture and sensitivity testing. Demographic and clinical data were collected. Self-reported ethnic origin was recorded. Deprivation was analysed on a postcode basis, using the 2015 English Indices of Deprivation, by means of average decile ranking (1–10). Ethnic and socioeconomic differences between patients exhibiting resistance and those fully sensitive/culture negative were explored. Results: A total of 107 patients, including 26 children, (61.7% female; median (range) age 37.5 (4–81) years; 43.9% Caucasian, 39.2% Asian), were sampled. Five were excluded (3 contaminated, 2 inappropriate samples). Forty of the remaining 102 samples yielded positive cultures; of these 6/40 were fully sensitive but 34 (33% of total sample) displayed antibiotic resistance, most commonly to metronidazole (91.2%), and/or clarithromycin (77.4%). Dual resistance was present in 52.9%. Resistance to amoxicillin (n=2) and levofloxacin (n=3) was also identified. The remaining 62 samples were culture negative. There were no differences in the age or sex distributions between the two cohorts. Likewise, there was no significant difference in the ethnic distribution between patients displaying antibiotic resistance and those sensitive/culture negative (Asian 47% vs. 35% Chi 2 P=0.25) (figure 1A). Deprivation analysis showed very similar average decile rankings in both patient groups although distribution was skewed to the deprived end of each domain in both (figure 1B). Conclusion: One-third of biopsy samples referred for sensitivity testing, during the study period, exhibited antibiotic resistance, most commonly to first and second line eradication therapies. No significant differences were observed in ethnicity or in deprivation between patients exhibiting resistance and those sensitive/culture negative. However, trends identified in this study need to be further explored. Abstract PTU-067 Figure 1 Comparative analysis of resistant vs. sensitive/no culture cohorts. (A) Ethnicity (B) Deprivation